Growth hormone regulates the sensitization of developing peripheral nociceptors during cutaneous inflammation. Issue 2 (February 2017) - Liu, Xiaohua; Green, Kathryn J.; Ford, Zachary K.; Queme, Luis F.; Lu, Peilin; Ross, Jessica L.; Lee, Frank B.; Shank, Aaron T.; Hudgins, Renita C.; Jankowski, Michael P.
Abstract : Abstract: Cutaneous inflammation alters the function of primary afferents and gene expression in the affected dorsal root ganglia (DRG). However, specific mechanisms of injury-induced peripheral afferent sensitization and behavioral hypersensitivity during development are not fully understood. Recent studies in children suggest a potential role for growth hormone (GH) in pain modulation. Growth hormone modulates homeostasis and tissue repair after injury, but how GH affects nociception in neonates is not known. To determine whether GH played a role in modulating sensory neuron function and hyperresponsiveness during skin inflammation in young mice, we examined behavioral hypersensitivity and the response properties of cutaneous afferents using an ex vivo hairy skin-saphenous nerve-DRG-spinal cord preparation. Results show that inflammation of the hairy hind paw skin initiated at either postnatal day 7 (P7) or P14 reduced GH levels specifically in the affected skin. Furthermore, pretreatment of inflamed mice with exogenous GH reversed mechanical and thermal hypersensitivity in addition to altering nociceptor function. These effects may be mediated through an upregulation of insulin-like growth factor 1 receptor (IGFr1) as GH modulated the transcriptional output of IGFr1 in DRG neurons in vitro and in vivo. Afferent-selective knockdown of IGFr1 during inflammation also prevented the observed injury-induced alterations in cutaneous afferents and behavioral hypersensitivity similar to that after GH pretreatment. These results suggest that GH can block inflammation-induced nociceptor sensitization during postnatal development leading to reduced pain-like behaviors, possibly by suppressing the upregulation of IGFr1 within DRG. Abstract : Growth hormone treatment reverses mechanical and thermal hypersensitivity during cutaneous inflammation in neonates possibly by suppressing primary afferent upregulation of insulin-like growth factor 1 receptor.Supplemental Digital Content is Available in the Text.